Cognitive Component in the Structure of Children's Subjective Well-Being - Bruk Zh.Yu; Ignatjeva S.V; Volosnikova L.M; Semenovskikh T.V (Moscow State University of Psychology and Education, 2021)
The subjective well-being of children today attracts researchers around the world and remains less studied than the subjective well-being of adults. The article presents the study of subjective well-being of 1719 schoolchildren from Tyumen at the age of 10 and 12 years. The research is a part of the International Survey of Children's Well-being (ISCWeB) - Children's Worlds. Family, children, their protection, support and provision of subjective well-being are fundamental values that determine world politics. The aim of the study was to analyze the cognitive component of children's subjective well-being, carried out using factor analysis. We assume that the cognitive component of subjective well-being arises with a holistic picture of the world, the current life situation in which the child is happy. To collect factual material a questionnaire was used, consisting of eight main spheres of children's life, reflecting the components of subjective well-being: social, material, physical, religious, psychological. The questions and judgments included in the questionnaire, revealed the specifics of the child's attitude to himself and the world around him. Cluster analysis in the plane of the identified patterns of subjective well-being (intrareflective, interreflective) made it possible to distribute children into groups. Children are happy if they can make choices, decide for themselves how to relate to life, society and themselves. "Conditionally happy" children are happy with what they have. They are the ones who are really happy in the offered life circumstances and know how to appreciate and enjoy what they have in life. "Conditionally unhappy" children think that they have everything, they give "socially acceptable" answers, but they are not happy. Social attitudes prevent the child from finding "balance" between the real, external and his own, internal world. Ideally, a child experiences subjective well-being when the intrareflective and interreflective components are in balance.